2020
DOI: 10.3390/jcm9030855
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Properties of Quercitrin-Coated Porous Ti-6Al-4V Implants for Orthopaedic Applications Assessed In Vitro

Abstract: (1) One strategy to improve the outcome of orthopedic implants is to use porous implants with the addition of a coating with an antibacterial biomolecule. In this study, we aimed to produce and test the biocompatibility, the osteopromotive (both under normal conditions and under a bacterial challenge with lipopolysaccharide (LPS)) and antibacterial activities of a porous Ti-6Al-4V implant coated with the flavonoid quercitrin in vitro. (2) Porous Ti-6Al-4V implants were produced by 3D printing and further funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…The use of a coating that is covalently linked to the surface, as demonstrated by FTIR spectroscopy and XPS in previous studies [18,19], could provide an alternative to the use of a polymer, which is considered as one of the leading causes of late stent thrombosis in DES [8,9]. Similar to previous reports [19,35], QR coated surfaces were also biocompatible on HUVEC cells, and remarkably showed higher metabolic activity in all evaluated time points, similar to other studies with mesenchymal stem cells [18,19]. This result is promising since a rapid endothelialization of the stent surface is very important in order to avoid thrombosis, a major complication of DES.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The use of a coating that is covalently linked to the surface, as demonstrated by FTIR spectroscopy and XPS in previous studies [18,19], could provide an alternative to the use of a polymer, which is considered as one of the leading causes of late stent thrombosis in DES [8,9]. Similar to previous reports [19,35], QR coated surfaces were also biocompatible on HUVEC cells, and remarkably showed higher metabolic activity in all evaluated time points, similar to other studies with mesenchymal stem cells [18,19]. This result is promising since a rapid endothelialization of the stent surface is very important in order to avoid thrombosis, a major complication of DES.…”
Section: Discussionsupporting
confidence: 75%
“…Most flavonoids are considered nontoxic and are present in plant-derived foods and present anti-inflammatory, antimutagenic and anticarcinogenic properties [37]. In previous studies, we have demonstrated that quercitrin coating presents good biocompatibility, osteopromotive, anti-inflammatory and antibacterial activity [18,19,35,36]. Here, we proved that quercitrin could also be applied as a coating for bare metal stents, and combined with the nanostructured surface, to overcome the main drawbacks of DES.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Hierarchical surface nano-topography and chemistry finely combined ensure outstanding anti-repellent properties based on (super-)hydrophobic features. Quercitrin-functionalized via wet chemistry of porous structure of Ti6Al4V orthopaedic implants allowed promoting osseointegration and preventing infection by decreasing bacterial adhesion by 75% [ 72 ]. Nanodiamond coating (at 0.075, 0.75, and 7.5% w / v ) onto additively manufactured selective laser melted Ti substrates synergistically promoted osseointegration and inhibit S. aureus adhesion by 88%, as shown in Figure 3 [ 73 ].…”
Section: Passive and Active Antibiofilm Treatmentsmentioning
confidence: 99%
“…Moreover, biomolecules also play an essential role in tissue repair process. Such as 5‐HMF (hydroxymethylfurfural), a bioreactor for proliferation and migration of human skin fibroblasts (HSF), which favored the wound healing 198 process, and quercitrin also demonstrated wide application including antibacterial and promoting bone cell proliferation 199 . Noteworthily, biomimetic elements‐based hydrogel will be more attractive.…”
Section: The Application Of Hydrogels In Localized Tumor Treatmentmentioning
confidence: 99%